1934
DOI: 10.1002/bjs.1800228506
|View full text |Cite
|
Sign up to set email alerts
|

Gastrojejunal ulceration

Abstract: OUR experience of the nature and frequency of gastrojejunal ulceration is of necessity short, for the first gastro-enterostomy was performed by Wolfler, at the suggestion of his assistant Nicoladoni, as recently as the year 1881. Possibly because the earlier operations were generally performed for carcinoma of the pylorus, the first case of gastrojejunal ulcer was not reported by Braung until 1899, this being one in which a fatal perforation took place. In the short period of thirty-five years that has ensued … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1938
1938
1977
1977

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…From then onwards he personally interviewed his old patients at a regular weekly clinic, at which it was later my privilege to assist. In 1934 he reported a 3.2% incidence of gastrojejunal ulcer in a large series of cases (Walton, 1934). This figure was the number of cases recognized by x-ray examination or by surgical exploration.…”
Section: Gastro-enterostomy and Duodenal Ulcermentioning
confidence: 95%
“…From then onwards he personally interviewed his old patients at a regular weekly clinic, at which it was later my privilege to assist. In 1934 he reported a 3.2% incidence of gastrojejunal ulcer in a large series of cases (Walton, 1934). This figure was the number of cases recognized by x-ray examination or by surgical exploration.…”
Section: Gastro-enterostomy and Duodenal Ulcermentioning
confidence: 95%
“…The rarest type of recurrent ulceration is suture-line ulcer, which usually occurs in subjects having very low acid outputs (19). It may follow any kind of gastric surgery in which nonabsorbable suture material is used in some layer of the gastric wall (10,19,22,26). The incidence after gastric resection is reported to be as low as 0.27N, but suture-line ulcers are increasingly recognized with the more widespread use of endoscopic techniques.…”
Section: Ulkusrezidiv Nach Magenresektion -Eine Gastrophotographischementioning
confidence: 99%
“…Other reports indicate that ulcers are most often fotmd in the line of the anastomosis (5, 23). One author has concluded that the recurrent ulcers always begin at the anastomotic line, because scarred tissue extending from the stoma to the ulcer was found in all instances (26). Histological study of 87 anastomotic ulcers revealed that the ulcer lay on the jejuna' side in 81, on the gastric side in 3 and on the anastomotic line in 3 cases (24).…”
Section: Ulkusrezidiv Nach Magenresektion -Eine Gastrophotographischementioning
confidence: 99%
“…A similar view was put forward by Balfour (1926), which he later modified. In recent years, however, an increasing number of surgeons have been advocating the use of partial gastrectomy in the treatment of anastomotic ulcer (Lewisjohn, 1930 ;Walton, 1934-5 ;Ginzburg and Mage, 1938 ;Finsterer, 1939 ;Fallis and Warren, 1946), and this is the operation which has been employed in nearly all of the present series; the main advantage of partial gastrectomy being that, up to the present, it is the only reliable way of permanently depressing the acid gastric secretion. Other methods have been introduced in recent years ; the extensive resection of the acid-secreting part of the stomach (Connell, 1934(Connell, , 1939Seely and Zollinger, 1935 ;Zollinger, 1940) ; and the resection of the vagi (Dragstedt and Schafer, 1945 ;Dragstedt and others, 1947; Thompson and James, 1947; Grimson and others, 1947) j but it is too early yet to assess their value.…”
Section: The Aetiological Basis Ofmentioning
confidence: 99%